Problematika Pengakuan Hak Ulayat Antara Pasal 3 UUPA dan PMATR/KaBPN Nomor 14 Tahun 2024 (RechtJiva, 2025)
This study examines the conflict of norms regarding the recognition of ulayat rights between Article 3 of the Basic Agrarian Law (UUPA) and Article 17(1) of the Minister of Agrarian Affairs and Spatial Planning/Head of BPN Regulation No. 14/2024. The background lies in the inconsistency between the UUPA’s communal recognition of ulayat rights and the conversion mechanism into individual ownership under PMATR/KaBPN No. 14/2024, which may trigger exploitation and internal conflict within indigenous communities. The research problem addresses the differing recognitions of ulayat rights under these two regulations. A normative legal method was employed with statutory, conceptual, and case approaches, alongside interpretive-descriptive, systematic, and prescriptive analytical techniques. Findings reveal that Article 3 of the UUPA upholds ulayat rights as collective rights for as long as the indigenous community exists, whereas Article 17 of PMATR/KaBPN No. 14/2024 permits conversion into group ownership, leading to privatization and weakening of communal order. The novelty lies in identifying two dimensions of conflict: recognition form clashes and potential degradation of communal land solidarity. It is concluded that PMATR/KaBPN No. 14/2024 contradicts UUPA principles, placing ulayat rights at risk of individualization. The study recommends reviewing technical regulations to honor communal values and strengthen protection mechanisms for indigenous collective rights.